Family influence on perinatal depression. (3rd August 2021) - Saraiva, Ana; Rosendo, Inês; Miguel, Susana; Duarte, Joana; Marques, Tiago; Baptista, Sylvie
Abstract: Background: The perinatal period is of big changes and adaptations for pregnant woman, making them more susceptible to depression. Perinatal depression can have huge negative consequences for the pregnant woman, child, family and society. Thus, the objective of this work is to understand the family influence in the appearance of this pathology. Methods: This is a cross-sectional observational study of a sample of pregnant women included for convenience, who answered a questionnaire with sociodemographic questions, pathological and physiological background and 4 scales: ERAP, EADS-21, FACES IV and ESSS. A descriptive analysis was carried out and then an inferential statistical analysis between the levels of depression, stress and anxiety and different variables. Results: The sample includes 41 pregnant women who agreed to participate in the study. It was found that only the family variables related to 'Satisfaction with the family' ( P = 0.024) and 'Intimacy' ( P = 0.006) seem to have significant relationship with the levels of perinatal depression. As possible confounding variables influencing these levels, we have the fact that pregnancy is planned ( P = 0.049), 'Satisfaction with friends' ( P = 0.001) and 'Social activities' ( P ≤0.001). Conclusions: It was proven that high levels of satisfaction with family and intimacy are protective factors for the development of perinatal depression. These family-related risk factors can be easily addressed in the context of family's doctor appointments and help to detect pregnant women at risk of perinatal depression. Deepening this knowledge will make it possible to prevent and intervene earlier in these cases and, consequently, reduce the harmful effects of this pathology.